(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Health is a priceless wealth for a person. Its preservation is entrusted to each of us. That is why taking care of one’s health is one of the obligatory actions. In the treatment of any disease, non-medication, that is, a method of treatment aimed at changing the lifestyle, is also important. Our way of life is a unique mirror that clearly shows the level of our medical culture. The importance of medical examination is that a timely medical examination makes it possible to always be healthy. A person who preserves and strengthens his health leads a healthy lifestyle and lives a long life. Modern medicine has the ability to treat many diseases. But we should not forget that it is easier to prevent the disease than to treat it. In this regard, timely medical examination prevents many diseases from progressing to serious levels and helps to maintain human health.